Pengaruh Ekuitas Merek, Kualitas Pelayanan, Dan Kualitas Produk Terhadap Minat Beli Ulang Pada Rumah Makan Rumah Ori Yogyakarta - Siti Mutiatun Naziah (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2025)
This study aims to determine the effect of brand equity, service quality and product quality on repurchase interest at Rumah Ori Restaurant Yogyakarta. This research was conducted in Yogyakarta in September – December 2021. The research method used quantitative, The population in this study were consumers of the Ori restaurant in Yogyakarta totaling 80 people. The sampling technique used was purposive sampling and accidental sampling. Techniques of data analysis with regression analysis significant level 5%. The results of hypothesis 1 obtained a t-count 2.141 > t-tabel, means that there is an influence of brand equity on repurchase interest, with a determinant coefficient of 23.59%. The results of hypothesis 2 t-count 2,119 > t tabel, means that there is an influence of service quality on repurchase interest, with a determinant coefficient of 21.69%. 3) The results of hypothesis 3, the t-count 2,257 > t tabel, means that there is an effect of product quality on repurchase interest, with a determinant coefficient of 15.52%. The results of hypothesis 4 obtained F count of 41.776, it was concluded that there was a significant influence between brand equity, service quality and product quality on repurchase interest, with overall determinant coefficient of 60.8%.